Food in the school curriculum in England: Its development from cookery to cookery - Owen-Jackson, Gwyneth; Rutland, Marion (Design and Technology Education: An International Journal, 2016)
The view of the authors is that the teaching of food in the school curriculum has varied throughout its history in order to meet political aims rather than educational ones. In this article they highlight the social and political changes that have influenced the teaching of food from its inception in the mid-1840s through to the present day. They argue that the political influences have been detrimental to the value of teaching about food and its potential for contributing to pupils’ overall education as well as what pupils should know, understand and learn about food and where it can be taught in schools. The teaching of food as cookery is traced from its introduction in the elementary school system, when it was for girls only, then to its development into domestic science, a subject for more academically able girls and the Sex Discrimination 1975 ensuring its availability for boys and girls. This was followed by the transformation into home economics, with a wider curriculum agenda, in the 1970s, the introduction of higher education degrees and the National Curriculum in 1990, which put food technology within design and technology. Changes within the National Curriculum are considered as are recent events impacting on the teaching of food, up to 2015 when GCSE Food Technology was replaced with GCSE Food and Nutrition and A Level Food Technology, which supports pupil progression into a range of food related degrees and careers, was removed. The article reviews a range of literature in order to consider the value of teaching food, the current situation in schools in England and the possible future role of food in the school curriculum.